2013
DOI: 10.1016/j.drugalcdep.2012.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Frontal systems deficits in stimulant-dependent patients: Evidence of pre-illness dysfunction and relationship to treatment response

Abstract: BACKGROUND Frontal systems dysfunction is present in stimulant-dependent patients. However, it is unclear whether this dysfunction is a pre-morbid risk factor or stimulant-induced, is severe enough to be clinically relevant, and if it is relevant to treatment response. These questions were addressed using the Frontal Systems Behavior Scale (FrSBe), a reliable and valid self-report assessment of three neurobehavioral domains associated with frontal systems functioning (Apathy, Disinhibition, and Executive Dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 51 publications
4
29
0
Order By: Relevance
“…Given a small base of research indicating that intact neurocognitive functioning might serve as a protective factor against adverse outcomes among high risk populations (Mitchell, Severtson, & Latimer, 2007), more research focused on the moderating effects of behavioral disinhibition on the association of exposure to neighborhood drug activity and marijuana use may prove beneficial. In addition, our findings support the utility of the FrSBe as a brief valid assessment for measuring frontally-mediated neurobehavioral traits relevant to substance use disorders (Lyvers et al, 2013;Winhusen et al, 2013). However, future studies aimed at examining the influence of neighborhood drug activity might benefit from more precise measures of neighborhood drug activity.…”
Section: Discussionsupporting
confidence: 70%
“…Given a small base of research indicating that intact neurocognitive functioning might serve as a protective factor against adverse outcomes among high risk populations (Mitchell, Severtson, & Latimer, 2007), more research focused on the moderating effects of behavioral disinhibition on the association of exposure to neighborhood drug activity and marijuana use may prove beneficial. In addition, our findings support the utility of the FrSBe as a brief valid assessment for measuring frontally-mediated neurobehavioral traits relevant to substance use disorders (Lyvers et al, 2013;Winhusen et al, 2013). However, future studies aimed at examining the influence of neighborhood drug activity might benefit from more precise measures of neighborhood drug activity.…”
Section: Discussionsupporting
confidence: 70%
“…Executive deficits have been observed in recreational users suggesting these deficits predate the development of addiction (Kollins, 2003;Soar, Mason, Potton & Dawkins, 2012). Frontal systems dysfunction has also been observed on selfreport measures of executive abilities prior to the development of stimulant abuse and to worsen with continued use (Winhusen, Somoza, Lewis, Kropp, Horigian, & Adinoff, 2013). Consistent with the suggestion that drugs of abuse can damage prefrontal cortical regions and produce deficits in executive function, several studies have reported links between the degree of drug exposure or dependence and neuropsychological and structural deficits (Ersche, Barnes, Jones,…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Studies in substance dependent populations have shown substantial yet differential deficits across the three FrSBe subscales suggesting widespread frontal deficits accompany drug addiction (Cattie, Woods, Iudicello, Pasada, Grant & TMARC Group, 2013;Winhusen et al, 2013;Verdejo-Garcı´, Rivas-Pe´rez et al, 2006). In this study, as with others (Lyvers et al, 2009;Spinella;, the FrSBe Disinhibition scale appears to be most predictive of alcohol,…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Alcohol and crack/cocaine is related to suicide attempts, with an increase of depressive symptoms and impulsivity [20][21] . Impulsivity with the use of alcohol has shown evidenced in the relationship of use with depressive symptoms and suicidality.…”
Section: Drugs Depression and Suicidementioning
confidence: 99%